Adsorption of Reactive Red 158 Dye by Chemically Treated Cocos Nucifera L. Shell Powder Adsorption of Reactive Red 158 by Cocos Nucifera L. - Mudhoo, Ackmez; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The effective removal of dyes from aqueous waste is an important issue for many industrialized countries. The traditional treatment methods used to remove dyes from wastewater have certain disadvantages such as incomplete dye removal, high reagent and energy requirements, and the generation of toxic sludge or other waste products that require disposal. The search for alternative and innovative treatment techniques has focused attention on the use of biological materials for dye removal and recovery technologies. This brief summarizes the latest developments in this important field.
Introduction -- Literature Data -- Synthetic Dyes -- Biosorption: a Green Remediation -- Adsorption Process -- Experimental Methodology -- Equilibrium Parameters of Adsorption -- Kinetic Modelling -- Batch Column Experiments -- Results and Discussions -- Conclusions -- References.
Keywords: Environmental sciences; Bioorganic chemistry; Chemical engineering; Environmental chemistry; Waste disposal; Environment; Environmental Chemistry; Waste Management/Waste Technology; Bioorganic Chemistry; Industrial Chemistry/Chemical Engineering